Photoluminescence and Point Defect Related Emission of ZnO:Mn2+ micro/nanorod Fabricated by Co-precipitation Method - Nguyen, Xuan Sang (H. : ĐHQGHN, 2018)
Herein we study point defects and correlation to photoluminescence in ZnO nanorod. ZnO mirco/nanorod structure was successfully fabricated by co-precipitation method with highly homogeneous characteristics. When ion Mn+2 introduced into ZnO structure, the d-spacing distance of ZnO was increased from 0.248 nm to 0.295 nm due to the larger ionic radius of Mn2+ in comparison to Zn2+. The photoluminescence emission evolution of ZnO through doping and annealing processes hinted the relation of point defect transformations. We found that zinc interstitial, zinc vacancy and its related defects were responsible mainly for photoluminescence emission in annealing and/or Mn2+ doped samples.